Freely Floating Fiat Money and Riba - Rab, Hifzur (University of Darussalam Gontor Press, 2024)
Rationally, logically and scientifically unit of measurement and unit of account must be precisely defined quantity of what is measured/accounted. Where such a unit doesn’t exist it ought to be the best available. This is also essential Shariah requirement. Money especially common medium of exchange is measure of value therefore it should be most stable measure of value. Price stability and ease in use as medium of exchange is money-ness (Thamaniah). Therefore common medium of exchange will be highly stable unless manipulated or where people are forced to use it. Monetary manipulation corrupts market mechanism that determine/set just/efficient prices and it is a massive fraud impermissible in Shariah. If government fails to address this problem people must use appropriate standard of value as unit of account. In case of gold and silver coins subject to debasement it is quantity of gold and silver respectively. In case of freely floating fiat money it amounts to accounting in real terms. Riba is measurable excess of quantity. In presence of monetary manipulation, money not being acceptable unit of account appropriate unit of account for money must be used and any excess as accounted will be profit in case the matter relate to profit and Riba in case it relate to lending or payment of dues. Use of appropriate unit of account will resolve most of the related real problems and modes of finance Shariah prefers will become efficient and viable while system of interest will not be able to continue its dominance. This will stifle fraud and corruption and remove basic cause of poverty and deprivation. It will support justice and righteousness and prevent marginalization institutions based on justice